Neonatal Iron Deficiency Causes Abnormal Phosphate Metabolism by Elevating FGF23 in Normal and ADHR Mice. (February 2014) - Clinkenbeard, Erica L; Farrow, Emily G; Summers, Lelia J; Cass, Taryn A; Roberts, Jessica L; Bayt, Christine A; Lahm, Tim; Albrecht, Marjorie; Allen, Matthew R; Peacock, Munro; White, Kenneth E
ABSTRACT Fibroblast growth factor 23 (FGF23) gain of function mutations can lead to autosomal dominant hypophosphatemic rickets (ADHR) disease onset at birth, or delayed onset following puberty or pregnancy. We previously demonstrated that the combination of iron deficiency and a knock‐in R176Q FGF23 mutation in mature mice induced FGF23 expression and hypophosphatemia that paralleled the late‐onset ADHR phenotype. Because anemia in pregnancy and in premature infants is common, the goal of this study was to test whether iron deficiency alters phosphate handling in neonatal life. Wild‐type (WT) and ADHR female breeder mice were provided control or iron‐deficient diets during pregnancy and nursing. Iron‐deficient breeders were also made iron replete. Iron‐deficient WT and ADHR pups were hypophosphatemic, with ADHR pups having significantly lower serum phosphate (p < 0.01) and widened growth plates. Both genotypes increased bone FGF23 mRNA (>50 fold; p < 0.01). WT and ADHR pups receiving low iron had elevated intact serum FGF23; ADHR mice were affected to a greater degree (p < 0.01). Iron‐deficient mice also showed increased Cyp24a1 and reduced Cyp27b1, and low serum 1, 25‐dihydroxyvitamin D (1, 25D). Iron repletion normalized most abnormalities. Because iron deficiency can induce tissue hypoxia, oxygen deprivation was tested as a regulator of FGF23, and was shown to stimulate FGF23 mRNA in vitro and serum C‐terminal FGF23 in normal rats in vivo. These studies demonstrate that FGF23 is modulated by iron status in young WT and ADHR mice and that hypoxia independently controls FGF23 expression in situations of normal iron. Therefore, disturbed iron and oxygen metabolism in neonatal life may have important effects on skeletal function and structure through FGF23 activity on phosphate regulation. © 2014 American Society for Bone and Mineral Research.